Government Actions And The Mineral Industry (The National Institute for Occupational Safety and Health (NIOSH), 1980)
New GSP Trade Status Approved.--President Carter, by Executive Order effective March 30, has approved Generalized System of Preference treatment for imports of nonferrous metal products and other imports from Ecuador, Indonesia, Zimbabwe, Uganda, and Venezuela. As of May 2, Afghanistan and Ethiopia will be taken off GSP status. Under the Generalized System of Preferences, certain imports from developing countries are provided duty-free treatment. A country can lose its GSP status if its shipments of the product exceed $41.9 million or more than 50% of total U.S. imports during the preceding year. However, the President can waive the 50% rule in cases where total U.S. imports of an item in 1979 were less than $1 million. Certain nonferrous imports from Mexico, Peru, Chile, and Zambia are already covered by GSP. Hearings April 10 on International Tin Agreement.--The Fifth International Tin Agreement of which the United States is a signatory, which entered into force on July 1, 1976, will expire on June 30, 1981. A negotiating conference for a Sixth International Tin Agreement will be held under auspices of the United Nations at Geneva from April 14 to May 16, 1980.